Simulasi Docking Senyawa Kurkumin dan Analognya Sebagai Inhibitor Reseptor Androgen pada Kanker Prostat - Arwansyah Arwansyah; Laksmi Ambarsari; Tony I Sumaryada (Current Biochemistry, 2014)
Curcumin, the major compound of Curcuma longa L, has been proven to have the toxicity effect on prostate cancer cell. This research was aimed to study the affinity and interaction of curcumin and its analogs as compettitive inhibitor to androgen hormon before working in vitro/in vivo research. Curcumin and its analogs were transformed into 3D structure, then docked to androgen receptor (3B67). The data of Gibbs energy (?G) value showed stability interaction between ligand and androgen receptor residues. The docking results showed that curcumin and its analogs have potential as inhibitor on androgen receptor. Based on results ?G score, analog 4 (1,7-bis-(3,4-dihydroxy-phenyl)-hepta-1,6-diene-3,5-dione) has highest potential as the inhibitor for androgen receptor.